Health in the Neighborhood and Household Contexts Among Older Chinese Americans. (December 2017) - Tang, Fengyan; Xu, Ling; Chi, Iris; Dong, Xinqi
Objective: This study examined the associations of neighborhood characteristics and living arrangements with physical and mental health among older Chinese Americans.Method: A sample of 3, 159 community-dwelling Chinese older adults in the Greater Chicago area provided reports of health, socio-demographic characteristics, living arrangements, social cohesion, and neighborhood disorder. We used multinomial logistic, Poisson, and negative binominal regression analyses.Results: Neighborhood disorder was consistently associated with negative health indicators, including poor self-reported health, more chronic conditions, depressive symptoms, and anxiety symptoms. Findings about the relationships between social cohesion and health indicators were mixed. Social cohesion was more salient to mental health for those living with spouse, children, and/or grandchildren relative to those living with spouse only.Discussion: Policies and interventions are needed to improve the physical and social environments of neighborhoods and to promote healthy aging among Chinese older adults and in the general population as well.